2000
DOI: 10.1159/000054149
|View full text |Cite
|
Sign up to set email alerts
|

Severe Thrombotic Complications Associated with Activated Protein C Resistance Acquired by Orthotopic Liver Transplantation

Abstract: We report a patient who developed recurrent hepatic artery thrombosis and deep venous thrombosis following orthotopic liver transplantation. Investigations revealed the presence of activated protein C (APC) resistance due to a mutation in the factor V gene in the transplanted liver. The patient’s own peripheral blood cells did not carry the mutation. Although part of factor V is located in the platelets and may be endogenously synthesized by megakaryocytes, this case demonstrates the major clinical importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
(12 reference statements)
3
12
0
Order By: Relevance
“…10 We recommend performing routine screening for APC resistance in patients who develop venous thrombosis after LT. In addition, we agree with Gillis et al, 8 who also suggested screening liver donors for the presence of APC resistance if they have a personal or family history of thromboembolic disease. Detection of this thrombophilic risk factor is crucial for making accurate decisions about thromboprophylaxis or anticoagulant therapy in liver transplant recipents with deep-vein thrombosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 We recommend performing routine screening for APC resistance in patients who develop venous thrombosis after LT. In addition, we agree with Gillis et al, 8 who also suggested screening liver donors for the presence of APC resistance if they have a personal or family history of thromboembolic disease. Detection of this thrombophilic risk factor is crucial for making accurate decisions about thromboprophylaxis or anticoagulant therapy in liver transplant recipents with deep-vein thrombosis.…”
Section: Discussionsupporting
confidence: 91%
“…6 Severe thrombotic complications (pulmonary embolism and inferior caval vein thrombosis) also have been described in a liver transplant recipient with a heterozygous protein C deficiency associated with dysfibrinogenemia. 7 Other investigators have reported such severe thrombotic complications as recurrent hepatic artery thrombosis and deep-vein thrombosis associated with APC resistance on the basis of a heterozygous fVL mutation acquired by LT. 8 In a retrospective study of 214 liver recipients, the risk for development of thrombosis after LT was increased in the presence of a heterozygous fVL mutation in the donor liver, but the relative risk for hepatic vessel thrombosis was found to be low. 9 Renal transplant recipients with an fVL mutation have an increased risk for renal transplant vein thrombosis, early graft loss, and acute vascular rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent anecdotal experiences suggest that transplantation of an fVL carrier liver into a normal recipient might lead to frank disease. [47][48][49][50] In summary, the role of liver transplantation for the thrombophilias in the absence of intrinsic liver disease is controversial. In fVL pediatric patients in whom the risk of thrombosis or actual thrombosis and its sequelae are significant, hepatic transplantation must be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports present similar cases of LT recipients who developed APC resistance from donors heterozygous for the factor V Leiden mutation. Their postoperative course was complicated by recurrent hepatic artery and deep vein thromboses . These cases suggest that APC resistance should be routinely screened for in all LDLT and that either heterozygosity or homozygosity precludes donation.…”
Section: Thrombotic Diseasementioning
confidence: 97%
“…These complications include the development or refractoriness of hyperammonemia, mental status changes, and lactic acidosis in the short term, significant hyperferritinemia or hyperlipidemia, or the development of de novo hypercoaguability or a bleeding diathesis. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) Such transmissions can be categorized in several ways: first, whether the transplant was performed using a live or deceased donor without pre-LT recognition of a disorder (ie, occult heterozygous urea cycle defects); and second, with a known pre-LT transmissible condition (cystic fibrosis [CF]) or a domino transplant (ie, familial amyloidotic polyneuropathy [FAP]). Finally, whether the donor had a known (ie, polycystic liver disease [PCLD]) or unrecognized forme fruste (ie, Ehlers-Danlos, alpha-1-antitrypsin [A1AT]) of heterozygosity for a transmissible disease.…”
mentioning
confidence: 99%